Modeling of hydrodynamic impact on underwater gas pipeline in A trench with liquefied soil - Gilyov, Evgeniy Evgenievich; Shubin, Sergey Nikolaevich; Borovkov, Aleksey Ivanovich; Abramian, Andrey Karenovich (Computational Continuum Mechanics, 2011)
The two-dimensional problem of standing wave impact on an underwater gas pipeline is discussed. The pipeline is placed in a trench filled with liquefied soil. The unsteady problem of the motion of heavy fluid is solved using the finite element method and the Lagrangian approach. A rheological model of dry friction represents pipe-to-soil adhesion. It is shown that the frame (liquefied soil) rigidity parameters and a dry friction force influence the pipeline oscillations.
Keywords: underwater pipe; standing wave; finite element method; dry friction model; liquefied soil